Methodological Aspects of Depreciation Accounting and Analysis of the Use of the Depreciation Policy - AMANOVA, Gulnara; SAPARBAYEVA, Saule; AKIMOVA, Bibigul; DAIRABAYEVA, Aizhan; KAZHMUКHAMETOVA, Assem; SADUAKASSOVA, Kunsulu; TULESHOVA, Gulnar (Journal of Advanced Research in Law and Economics; Vol 7 No 3 (2016): JARLE, Volume VII, Issue 3(17), Summer 2016, 2016)
The purpose of this paper is to develop an evidence-based approach to the management of the company’s depreciation policy through the refinement of existing techniques and the development of guidelines on the mobilization of depreciation tools to provide the financial source for the reproduction of fixed assets. The problem of the management of depreciation tools, which help to ensure the reproduction of fixed capital, is currently relatively new. This is due to the fact that domestic and foreign economists suggest different approaches to the nature of depreciation as an economic category and its role in the reproduction of capital. However, there are few publications associated with the development of the strategy of the company’s depreciation policy to provide financial resources, investment and innovation activities. Also, there are a number of unexplored or controversial issues that need to be addressed. Therefore, in this research, the authors consider the development of scientific bases for the accumulation of cash depreciation expenses for their subsequent investment in fixed assets through the management of the company’s depreciation policy. This study is based on the general scientific methods of knowledge (observation, comparison, description, classification, generalization and specification), as well as grouping, systematizing and the methods of economic, financial and statistical analysis.